Overview of Patient Safety Culture Among Nurses in Providing Services at Hospital - Karimah, Wasiatul; Porusia, Mitoriana (Sarana Ilmu Indonesia (salnesia), 2025)
Nurses play a vital role in maintaining patient safety as they are at the frontline of healthcare services. Patient safety culture needs to be measured as an indicator of service quality. This study aimed to describe the patient safety culture among nurses at the Research Partner Hospital. This study was conducted at a Type C General Hospital located in Sukoharjo, using a descriptive quantitative method and a cross-sectional design. The sample consisted of 167 nurses selected through purposive sampling, with data collected via the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. The results showed that the patient safety culture was categorized as